The Effect of Immersion Eggs with Different Doses of Vitamin C on Fertilization Rate andHatchabilityof Gouramy Eggs (Osphronemus gouramy Lac.) - Hafizha, Sannada; Nuraini, Nuraini; Aryani, Netti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study was conducted on February-March 2020 at the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine, University of Riau, Pekanbaru.The purpose of this study was to determine the effect of immersion eggs with different doses of vitamin C on hatchability, growth, and survival of gouramy larvae.This study used a Completely Randomized Design (CRD) with 5 treatments and 3 replications. Different doses used on this study were;C0 (0 mg / L), C50 (50 mg / L), C100 (100 mg / L), C150 (150 mg / L) and C200 (200 mg / L). Immersion of gouramy egss with vitamin C for 3 hours with density 150 eggs and water volume 5 L.The results showed that different dose of vitamin C solution had a significant effect (P <0.05) on fertilization rate (98.22%) and hatching rate (94.81%).The best dose of vitamin C to increase the fertilization rate and hatching rate was 200 mg/L.The quality of water during the study were temperature 26.3-28.2 ºC, pH of immersion water 5.5-5.8, pH of hatching water 5.9-6.3, pH of larvae maintenance water 5.7-6.5 and DO 6.0-6.6 mg/L.Keywords : Gouramy Fish,Vitamin C,Fertilization rate, Hatching rate,